Investigating the effect of Affective Commitment on Employees’ Resistance to Change through the Mediating Role of Attitudes and Readiness for Change - Nafiseh Sadr; Alireza Khorakian; Gholamreza Malekzadeh (مطالعات مدیریت بهبود و تحول, 2020)
Organizations have to innovate and change in current dynamic and complex environment. Organizational change studies show that employees don’t associate in organizational changes and resist to change most of the times. Resistance to change will result to the failure in changing plans. In this study, we are going to investigate the effect of affective commitment on resistance to change through the mediating role of attitudes toward change and readiness for change among the Mellat Bank employees of Mashhad. The descriptive-survey research strategy has been used to conduct study. Data was collected by a standard measurement and was performed by employing AMOS and SPSS. Face validity and content validity were used for testing the validity of measurement and Cronbach’s Alpha for testing the reliability of data. The findings suggest that affective commitment has effects on Resistance to change. Furthermore, the mediating role of attitude towards change and readiness for change-as one of the neglected cases in previous studies-was confirmed.